#Baghjanburns : crisis at Oil India Ltd - Kaul, Asha, (SAGE Business cases., 2024)
This case delves into managing a multifaceted crisis within a stakeholder ecosystem. It highlights a public sector company, Oil India Ltd (OIL), dealing with a well blowout that escalated into a prolonged environmental and reputational disaster. As the crisis extended for 190 days, the company faced complex challenges stemming from technical and stakeholder-related factors. Mishra, OIL’s Chairman and Managing Director, assigned Roy to investigate the crisis’s root causes and pondered if it could have been managed differently. The intricate interplay of technical and non-technical aspects, past and present, and various contributors created a uniquely challenging crisis scenario. Roy aimed to identify the triggers and lessons from this unprecedented event.